Delays in Post-Remission Chemotherapy for Philadelphia Chromosome Negative Acute Lymphoblastic Leukemia are Associated with Inferior Outcomes in Patients who Undergo Allogeneic Transplant: An Analysis from ECOG 2993/MRC UK ALLXII. - Kumar, A; Gimotty, P; Gelfand, J; Buck, G; Rowe, J; Goldstone, A; Fielding, A; Marks, D; Litzow, M; Paietta, E; Lazarus, H; Tallman, M; et al. (Wiley, 2016)
Adults with acute lymphoblastic leukemia (ALL) have a poorer prognosis than children due to a high risk of relapse. One explanation may be variable adherence to dose-intense chemotherapy. However, little is known about risk factors for delays in therapy and their impact on survival. We conducted an analysis of ECOG 2993/UKALLXII trial to study delays in post-remission chemotherapy in adults with newly-diagnosed ALL. Logistic regression was used to identify risk factors for a very long delay (>4 weeks, VLD) in start of intensification therapy. Cox regression was used to evaluate the impact of delays on overall and event-free survival (OS, EFS). We evaluated 1076 Philadelphia chromosome negative (Ph-) patients who completed induction chemotherapy, achieved complete remission, and started intensification. Factors independently associated with VLD included: duration of hospitalization (Odds Ratio (OR)=1.2, p<0.001) during Phase I; thrombocytopenia during Phase I (OR=1.16, p=0.004) or Phase II (OR 1.13, p=0.001); chemotherapy dose reductions during induction Phase I (OR=1.72, p<0.014); female sex (OR=1.53, p=0.010); Black (OR=3.24, p=0.003) and Asian (OR=2.26, p=0.021) race; and increasing age (OR=1.31, p<0.001). In multivariate Cox regression, patients who underwent allogeneic stem cell transplant (alloHCT) had significantly worse OS (HR 1.4, p=0.03) and EFS (HR 1.4, p=0.02) after experiencing a VLD compared to alloHCT patients who experienced <=4 weeks delay. This article is protected by copyright. All rights reserved.